2015
DOI: 10.1177/0309133315582045
|View full text |Cite
|
Sign up to set email alerts
|

Toe-cut terraces

Abstract: Alluvial fans and fluvial terraces occur in nearly all climatic settings and often coexist within the same drainage basin. These landforms play an important role in understanding the geomorphic, hydrologic, sedimentologic and erosional histories of a basin. The juxtaposition of fans and fluvial terraces, in some instances, can lead to misinterpretation in distinguishing traditional fluvial terraces from the truncated toe of tributary alluvial fans. This becomes particularly troublesome for those attempting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 99 publications
0
2
0
1
Order By: Relevance
“…These toe cuts are formed by lateral erosion of the axial BMR rather than by vertical incision and base-level change in the main river. Also, several studies (Leeder & Mack, 2001;Larson et al, 2015;Giles et al, 2018) in the Basin and Range extensional region (USA) have shown that toe-cuts are an important indicator of high tectonic activity. The smaller alluvial fans are observed at the south margin of the BMG.…”
Section: Modern Alluvial Fans (Qmaf)mentioning
confidence: 99%
“…These toe cuts are formed by lateral erosion of the axial BMR rather than by vertical incision and base-level change in the main river. Also, several studies (Leeder & Mack, 2001;Larson et al, 2015;Giles et al, 2018) in the Basin and Range extensional region (USA) have shown that toe-cuts are an important indicator of high tectonic activity. The smaller alluvial fans are observed at the south margin of the BMG.…”
Section: Modern Alluvial Fans (Qmaf)mentioning
confidence: 99%
“…Las terrazas fluviales de agradación son remanentes de antiguas llanuras aluviales que han quedado elevadas en relación con el río actual y su llanura aluvial. Episodios de incisión y depositación pueden dar lugar a una serie de terrazas de diferentes alturas (Larson et al, 2015) que representan descensos del nivel de base del río vinculados, en general, a cambios climáticos o ascensos tectónicos.…”
Section: Marco Geomorfológico Y Secuencia Estratigráficaunclassified
“…The upland of terrace in valley fill is like a fill-cut terrace. The lower remain terrace are cut terraces (Larson et al, 2015).…”
Section: Geomorphology Of Meandering and Low Gradient Landformsmentioning
confidence: 99%